2019
DOI: 10.1063/1.5061714
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced local symmetry breaking upon liquid–liquid transition of GeI4 and SnI4

Abstract: SnI4 and GeI4 have been confirmed to have another liquid state appearing on compression. To identify the microscopic pathway from the low- to high-pressure liquid states, the structure of these liquids in the appropriate thermodynamic regions was analyzed using a reverse Monte Carlo method. The occurrence of pressure-induced symmetry lowering of molecules, from regular tetrahedral to ammonia-like pyramidal symmetry, was then recognizable in these systems. This symmetry lowering is reflected in the change in sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…We did not also consider a small wavenumber region, which may affect the performance of RMC fit unless the precise density is known. Thus, we chose the same lower bound, k 1.5 Å −1 , that has been used for the liquid SnI 4 analysis [15]. Table 1 lists the actual wavenumber region adopted for each S(k).…”
Section: Rmc Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not also consider a small wavenumber region, which may affect the performance of RMC fit unless the precise density is known. Thus, we chose the same lower bound, k 1.5 Å −1 , that has been used for the liquid SnI 4 analysis [15]. Table 1 lists the actual wavenumber region adopted for each S(k).…”
Section: Rmc Fitmentioning
confidence: 99%
“…The following two paradoxical aspects of SnI 4 molecules regarding the polyamorphic behavior have been posed: while SnI 4 molecules retain their regular tetrahedral symmetry within the CP-I field even close to the melting point and up to the boundary between CP-II [14], they lower symmetry from T d (regular tetrahedral) to C 3v (a regular tetrahedron squashed in one direction) upon the LLT [15]. (Note that the molecular symmetry of C 3v is still compatible with CP-I's crystalline symmetry of Pa 3.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of a specific bond length r, (3) reads as follows: p(r, T) = C 0 (T)r −6 + C 1 (T)r −9 + C 2 (T)r −12 , (A. 1) where the set of temperature-dependent coefficients {C i (T)} are to be determined.…”
Section: Appendix Construction Of the Molecular Eosmentioning
confidence: 99%
“…We have recently revealed that SnI 4 molecules are squashed in one direction upon compression, changing their point symmetry from T d to C 3v , when they experience the pressureinduced liquid-liquid transition [1]. It is then of interest to examine whether such a molecular peculiarity develops below the melting point.…”
Section: Introductionmentioning
confidence: 99%
“…It is proposed that the CP-II phase belongs to the 𝑃1 ̅ space group and is composed of edge sharing Sn-I octahedrons disposed in a zigzag ribbon along the b-axis. Very recently, an EXAFS study has been published as a function of pressure and temperature up to 9 GPa and 900 K 24 , in the goal of determining a possible deformation of the SnI 4 tetrahedron in the solid phase before the melting, where a transformation from the T d to the C 3v point group has been observed 25 . From these results, the coordination number does not change up to 9 GPa, and the intramolecular distances are in good agreement with the published results 26 , giving a "molecular modulus" of 157 GPa at ambient pressure and temperature.…”
Section: Introductionmentioning
confidence: 99%